مخطوط“تقييد في أصول الدين والفقه“ لابن الفتوح التلمساني - زاوي, بوبكر (جامعة الوادي - University of Eloued, 2023)
لقد كان العصر الوسيط مرحلة بروز مذاهب فقهية مختلفة حازت كل منها على مجال جغرافي واجتماعي ساهم في انتشارها، وكان أن المذهب المالكي حاز القبول من ساكنة المغرب الأوسط كاتجاه فقهي حافظوا من خلاله على تماسكهم الروحي والاجتماعي تتوخى هذه المساهمة التعريف بأحد أعلام الفقه المالكي بالمغرب الأوسط الزياني وهو الشيخ محمد ابن عمر بن الفتوح ( ت 818ه/1415م)، وذلك من خلال تقديم أحد مؤلفاته المخطوطة الهامة المسماة: " تقييد في أصول الدين والفقه"، وهو مخطوط ثمين، يظهر لنا من خلاله سعة علم الشيخ وتمرسه في الفقه المالكي من جهة، ويعطي صورة واضحة كذلك على المنحى العقيدي الذي سارت عليه أقطار الغرب الإسلامي آنذاك بتبنيها للعقيدة الأشعرية . حاولنا في البداية تقديم ملمح عام عن نشاط الفقه المالكي بالمغرب الأوسط وركزنا على تتبع مسار حركة التأليف فيه باعتباره أهم مظهر من مظاهر نشاط أي مذهب وذلك بتوظيف المنهج الإحصائي الكمي، ثم حرصنا على جمع شتات ترجمة المؤلف وتقديم تعريف واضح المعالم حول شخصيته، ثم قدمنا المخطوط من خلال التعريف به ومحتواه وقيمته العلمية والتاريخية. The Middle Age was the emergence of different doctrines-madhhab -of al-Fiqh, each with a geographical and social domaine.As the Maliki madhhab was accepted by the inhabitants of the Middle Maghreb which allowed them to maintain their spiritual and social cohesion. This contribution seeks to introduce a scholar of Maliki jurisprudence to the Middle Maghreb, Sheikh Muhammad Ibn Umar Ibn al-Fotouh (d.818 AH/1415 CE), through the presentation of one of his manuscript books, entitled "A restriction on the origins of religion and jurisprudence – Fiqh-" which is a precious manuscript through which the knowledge of the Sheikh and his experience in al-Fiqh Maliki on the one hand show us the knowledge of the Sheikh. It also gives a clear picture of the orientation of Muslim in the West countries by adopting the Ash'ari creed. We initially tried to present an overview of al-Maliki fiqh activity in the Middle Maghreb and focused on tracking the process of his authorship as the most important manifestation of any madhhab activity by employing the curriculum The quantitative statistics, then we collected the author's translation diaspora and provide a clear definition of his personality, then presented the manuscript by introducing it, its content , scientific and historical value.
نموذج من التراث الفقهي المغمور بالمغرب الأوسط
مقال
Keywords: الفقه المالكي؛ المغرب الأوسط؛ ابن الفتوح؛ تقييد أصول الدين؛ تلمسان فاس; al-Fiqh Maliki; middle Maghreb ; Ibn al-Fotouh ; A restriction origins of religion; tlemcen fes